Success/Failure in Higher Education: How Long Does it Takes to Complete Some Core 1st. Year Disciplines? - CHAGAS LOPES, Margarida; FERNANDES, Graça Leão (Journal of Research in Educational Sciences; Vol 1 No 1 (2010): JRES Volume I Issue 1(1) Summer 2010, 2010)
Despite the enormous increasing in Higher Education (HE) enrolment during the last decades in Portugal, retention rates remain very high when compared to most European Union countries'. This outcome is particularly meaningful for a set of 1st year's critical matters which failure severely conditions subsequent success as they are part of the scientific domain's basic knowledge. In this paper we investigate this feature for ISEG (School of Economics and Management of the Technical University of Lisbon) and consider its Pedagogic Observatory database which includes more than 1,500 individual data relative to the four graduation programmes. As relative failure expresses frequently under the form of longer time spells needed to complete those disciplines in this paper we adjusted a duration model (with control group)in order to assess the main determinants of the "survival" probabilities. After having controlled for ability, the results we obtained from Cox Regression show that the economic and social status of the family of origin, especially mother's and father's school level and occupation go on influencing students' results although not so meaningfully as in previous educational phases. Also the specific graduation track – Economics, Management, and Mathematics applied to Economics, Management and Finances – appear to be deeply associated with success or retention. Nevertheless, the main determinant of relative success/failure is the student's situation towards the labour market, a meaningful proportion of them having to perform a paid occupation to afford to pay for education costs. Therefore our policy recommendations are twofold: i) to shed light on the need for a more robust Government's Social Policy towards HE students especially now that the Bologna Reform imposes an heavier budgetary burden upon students; ii)to emphasize the financial, organizational and syllabuses' reforms that HE institutions need to develope in order to capture and keep the "new publics" namely adult students for whom combining study and paid work represents the only available funding source.